Induced paternal effects mimic cytoplasmic incompatibility in Drosophila. - Clark, M.E.; Heath, B.D.; Anderson, C.L.; Karr, T.L. (Genetics, 2006)
Wolbachia is an intracellular microbe found in a wide diversity of arthropod and filarial nematode hosts. In arthropods these common bacteria are reproductive parasites that manipulate central elements of their host's reproduction to increase their own maternal transmission in one of several ways. Cytoplasmic incompatibility (CI) is one such manipulation where sperm are somehow modified in infected males and this modification must be rescued by the presence of the same bacterial strain in the egg for normal development to proceed. The molecular mechanisms involved in the expression of CI are unknown. Here we show that Wolbachia infection results in increased mRNA and protein expression of the Drosophila simulans nonmuscle myosin II gene zipper. Induced overexpression of zipper in Wolbachia-free transgenic D. melanogaster males results in paternal-effect lethality that mimics the fertilization defects associated with CI. Likewise, overexpression of the tumor suppressor gene, lethal giant larvae [l(2)gl], results in egg lethality and a CI phenotype. Stoichiometric levels of zipper and l(2)gl are required for proper segregation of cellular determinants during neuroblast stem cell division. Taken together these results form the basis of a working hypothesis whereby Wolbachia induces paternal effects in sperm by manipulating the expression of key regulators of cytoskeletal activity during spermatogenesis.